Respon Pertumbuhan dan Hasil Bawang Merah (Allium cepa L.) Akibat Pemberian Biochar Sekam Padi dan Pupuk NPK pada Tanah Gambut (Fakultas Pertanian Universitas Tanjungpura, 2026)
Shallot (Allium cepa L.) is a high-value horticultural commodity, but its production in West Kalimantan remains low. The use of extensive peatlands could increase production. However, cultivation on peat soil is constrained by low fertility and high acidity. This study aimed to determine the effects and identify the optimal interaction dose between rice husk biochar and NPK fertilizer on shallot growth and yield on peat soil. The experiment was conducted at the Experimental land of the Faculty of Agriculture, Tanjungpura University, from November 2024 to February 2025 using a factorial Completely Randomized Design (CRD) with two factors. The first factor was rice husk biochar applied at three levels: 10, 20, and 30 tons/ha. The second factor was NPK fertilizer at three levels: 200 kg/ha, 300 kg/ha, and 400 kg/ha. Nine treatment combinations were tested with three replications and four plant samples per replication, resulting in a total of 108 observed plants. The results showed no significant interaction between biochar and NPK across all observed variables. Application of rice husk biochar at 30 tons/ha significantly affected plant height, number of bulbs per clump, fresh and air-dry bulb weight, and plant dry weight, but had no significant effect on the number of leaves. NPK fertilizer at 200 kg/ha significantly affected only the number of leaves.